2015
DOI: 10.3892/ijo.2015.2935
|View full text |Cite
|
Sign up to set email alerts
|

Antitumorigenic effect of plumbagin by induction of SH2-containing protein tyrosine phosphatase 1 in human gastric cancer cells

Abstract: A recent study reported that plumbagin downregulated the activity of Janus kinase 2 (JAK2)-signal transducer and activator of transcription 3 (STAT3) pathway to show various antitumor effects in multiple myeloma cells. We aimed in this in vitro study to demonstrate the inhibition of JAK2/STAT3 pathway by plumbagin through inducing SH2-containing protein tyrosine phosphatase 1 (SHP1) expression in the MKN-28 gastric cancer cell line. We performed western blot analysis to measure SHP1, phosphor-JAK2/STAT3 level,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…Targeting STAT3 signaling represents an important molecular mechanism for the anticancer activity of plumbagin in melanoma (18), gastric cancer (17), breast cancer (8), and prostate cancer (25). In line with these studies, the present data demonstrated that plumbagin treatment significantly suppressed STAT3 activation in EScc cells.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Targeting STAT3 signaling represents an important molecular mechanism for the anticancer activity of plumbagin in melanoma (18), gastric cancer (17), breast cancer (8), and prostate cancer (25). In line with these studies, the present data demonstrated that plumbagin treatment significantly suppressed STAT3 activation in EScc cells.…”
Section: Discussionsupporting
confidence: 88%
“…Plumbagin has exhibited anticancer properties in many types of cancer, including breast cancer (8), pancreatic cancer (9), prostate cancer (16), and gastric cancer (17). It has been reported that plumbagin can block prostate carcinogenesis triggered by loss of phosphatase and tensin homolog (PTEN) (16).…”
Section: Discussionmentioning
confidence: 99%
“… 39 A previous study demonstrated that gastric cancer cells expressing high levels of STAT3 also expressed high levels of VEGF, indicating a positive correlation between the expression levels of STAT3 and VEGF. 40 This is consistent with our findings that blocking STAT3 signal significantly inhibited TMEM119-induced VEGF expression in gastric cancer cells, which resulted in decreased cell migration and invasion. Moreover, blocking the activation of STAT3 in gastric cancer cells resulted in corresponding decrease in VEGF protein expression, which in turn resulted in decreased metastasis and invasion of gastric cancer cells.…”
Section: Discussionsupporting
confidence: 93%
“…Complementary DNA (cDNA) was subsequently produced using a high‐capacity cDNA reverse transcription kit (Applied Biosystems, Foster City, CA, USA) and treatment with 1 U DNase (Promega Corp., Madison, WI, USA). Reverse transcription polymerase chain reaction (RT‐PCR) was performed using a previously described method with modification . Briefly, 20 ng of cDNA was used to generate 25 μL of PCR product using Econo Taq ® PLUS Green Master Mix (Lucigen Co., Middleton, WI, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Reverse transcription polymerase chain reaction (RT-PCR) was performed using a previously described method with modification. 18 Briefly, 20 ng of cDNA was used to generate 25 μL of PCR product using Econo Taq ® PLUS Green Master Mix (Lucigen Co., Middleton, WI, USA). PCR was performed under the following conditions: initial denaturation at 94°C for 2 min, followed by 40 cycles of denaturation at 94°C for 15 s, annealing at 55°C for 15 s, and extension at 72°C for 15 s, and a final extension at 72°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%